Human iPSC-MSC-Derived Xenografts Modulate Immune Responses by Inhibiting the Cleavage of Caspases. (18th May 2017) - Li, Cheng-Lin; Leng, Yun; Zhao, Bin; Gao, Chang; Du, Fei-Fei; Jin, Ning; Lian, Qi-Zhou; Xu, Shuang-Yue; Yan, Guo-Liang; Xia, Jun-Jie; Zhuang, Guo-Hong; Fu, Qing-Ling; et al.
Abstract : Mesenchymal stem cells (MSCs) negatively modulate immune properties. Induced pluripotent stem cells (iPSCs)-derived MSCs are alternative source of MSCs. However, the effects of iPSC-MSCs on T cells phenotypes in vivo remain unclear. We established an iPSC-MSC-transplanted host versus graft reaction mouse model using subcapsular kidney injection. Th1, Th2, regulatory T cells (Treg), and Th17 phenotypes and their cytokines were investigated in vivo and in vitro. The role of caspases and the soluble factors involved in the effects of MSCs were examined. We found that iPSC-MSC grafts led to more cell survival and less infiltration of inflammatory cells in mice. iPSC-MSC transplantation inhibited T cell proliferation, decreased Th1 and Th2 phenotypes and cytokines, upregulated Th17 and Treg subsets. Moreover, iPSC-MSCs inhibited the cleavage of caspases 3 and 8 and inhibition of caspases downregulated Th1, Th2 responses and upregulated Th17, Treg responses. Soluble factors were determined using protein array and TGF-β1/2/3, IL-10, and MCP-1 were found to be highly expressed in iPSC-MSCs. The administration of the soluble factors decreased Th1/2 response, upregulated Treg response and inhibited the cleavage of caspases. Our results demonstrate that iPSC-MSCs regulate T cell responses as a result of a combined action of the above soluble factors secreted by iPSC-MSCs. These factors suppress T cell responses by inhibiting the cleavage of caspases. These data provide a novel immunomodulatory mechanism for the underlying iPSC-MSC-based immunomodulatory effects on T cell responses.